Impact of additional abdominal approach to transanal one stage endorectal pull-through in treatment of Hirschsprung’s disease - Huu Thien, Ho; Xuan Thanh, Cao; Thanh Xuan, Nguyen; Huu Son, Nguyen (International Surgery Journal, 2019)
Background: The transanal one-stage endorectal pull-through (TOSEPT) procedure sometimes requires assistance by an abdominal approach to complete the operation. This study aims to rectify this by evaluating the impact of an assisted abdominal approach in the outcomes of the TOSEPT in children with HD. Methods: A retrospective study was conducted at surgical paediatric department of Hue central hospital. All consecutive medical records of patients operated on for HD in our department between June 2010 and June 2018 were retrieved and analysed. Results: 66/446 (14.79%) patients with HD who required TOSEPT with an additional abdominal approach to complete the operation for inclusion in this retrospective study. Length of the resected colon: 13.30±3.45 cm (open group) and 19.70±4.50 cm (laparoscopic group). Average operative time: 156±12 minutes (open group) and 170±14 minutes (laparoscopic group). No deaths or intra-operative complications were recorded in this study. No postoperative complication occured in the laparoscopic group. Grade II complication based on Dindo-Clavien classification occurred in 14 (21.21%) of the open group and one (1.51%) grade III complication. The length of hospital stay was shorter in the laparoscopic group at 5±1.5 days compared to 7±2.5 days for the open group. All of the complications were grade I or II, mainly enterocolitis at 3-month follow-up. Conclusions: Additional abdominal approach impacts on post-operative results of TOSEPT procedure for HD but not on outcome of disease. Laparoscopic surgery as the additional abdominal approach should be used to reduce the complications.